Standing to Sue, Enforceable Title and Corporate Spin-Off: A Critique to the “Assertion Theory” - Valenzuela, Gabriella (2024)
This article aims to criticize the so-called “assertion theory” of civil procedure standing to sue, accepted by a significant part of the Peruvian jurisprudence, and consecrated by the Peruvian Civil Procedure Code. The paper seeks to show that this theory should be discarded since it has several conceptual problems, furthermore, it is not capable of giving an account of actual judicial practice when analyzing and deciding on the presence or absence of standing to sue. This becomes more noticeable in the field of judicial enforcement, and, to that extent, an example of corporate spin-off will be given to show that proving the existence of standing to sue concerning enforcement title can be complex, but that is essential for the judge to carry out this analysis.